2012
DOI: 10.1039/c2jm30242j
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the photo-bias stability of the Zn–Sn–O field effect transistors by an ozone treatment

Abstract: Highly improved negative bias illumination stress stability was achieved in a Zn-Sn-O field effect transistor after an ozone (O 3 ) treatment. The untreated ZTO FET exhibited a huge negative threshold voltage shift of 4.2 V but the O 3 treated device exhibited superior stability under NBIS conditions: the V th value of the O 3 treated ZTO FET for 600 s showed almost no change (DV th ¼ À0.07 V) under the same NBIS. The improvement in NBIS stability of the O 3 treated ZTO FETs was attributed to the lower oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 29 publications
2
60
0
1
Order By: Relevance
“…The SS value was as low as 0.27 V/decade for 2.5Z1T channel as shown in inset of Fig. 3b and this value is comparable or better than other reports for ZTO transistors 8,9,11 The minimum off-current was generally in the range of 10 -13 -10 -14 A, which is below the maximum level of 10 -12 A for flat-panel displays. 1 The Zn/Sn ratio clearly influenced the mobility of the transistors.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The SS value was as low as 0.27 V/decade for 2.5Z1T channel as shown in inset of Fig. 3b and this value is comparable or better than other reports for ZTO transistors 8,9,11 The minimum off-current was generally in the range of 10 -13 -10 -14 A, which is below the maximum level of 10 -12 A for flat-panel displays. 1 The Zn/Sn ratio clearly influenced the mobility of the transistors.…”
supporting
confidence: 76%
“…The I ON /I OFF ratio was as high as ~10 9 -10 10 , which is comparable to or better than other reports for well-6 behaved transistors. 9,11 The I ON /I OFF ratio derived from the transfer curve for V DS of 20 V showed clear decreasing trend with decreasing Zn/Sn ratio; it was ~10 9 -10 10 for 3Z1T, 2.5Z1T, and 2Z1T and it decreased to ~10 7 -10 8 and further to ~10 6 for 1Z1T and 1Z2T, respectively. Turn-on voltage, 5 the gate voltage at the onset of the initial sharp increase in a transfer curve, was mainly at 0 -3 V except 1Z2T transistor, which was largely negative-shifted (-9 V).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a similar approach, the ozone treatment was also shown to reduce the oxygen deficiency concentration in the ZTO film. 76 Similar to oxygen HPA and the oxygen plasma treatment, an ozone treatment can annihilate the oxygen deficiencies of the ZTO film and prevent the NBIS-induced instability of the resulting ZTO TFTs. On the other hand, the surface of the evaluated ZTO film were not encapsulated, the retarded desorption of adsorbed oxygen species was partially responsible for the improvement in NBIS stability.…”
Section: How To Reduce the Nbis Instabilitymentioning
confidence: 99%
“…72 To improve the NBIS stability of metal oxide TFTs, the control of oxygen nonstoichiometry in the metal oxide semiconductor was also attempted based on the mechanism of photoionization of oxygen vacancy defects. Because the photoionization of V O to V 2þ O responsible for NBIS degradation is proportional to the concentration of preexisting V O defects in the channel layer, the intentional supply of oxygen species, such as high pressure annealing (HPA), 34,73,74 oxygen-containing plasma treatment, 75 and ozone radical treatment, 76 into the oxygen deficient channel region would result in a decrease in [V O ], leading to the suppression of NBIS-induced V th instability. This group reported that the removal of the V O defect centers using intentional oxygen diffusion results in the strong suppression of NBIS instability in IGZO TFTs, as shown in Fig.…”
Section: How To Reduce the Nbis Instabilitymentioning
confidence: 99%